Anxious‐depressive attack and rejection sensitivity-Toward a new approach to treatment‐resistant depression - Hisanobu Kaiya (Wiley, 2024)
Abstract This paper aimed to find clues to treatment‐resistant depression (TRD) solutions. Depression comorbid with anxiety is often treatment‐resistant where anxious‐depressive attack (ADA) often lurks. ADA is a recently proposed clinical idea for just a psychological version of a panic attack. It mostly begins with an abrupt surge of intense anxiety followed by uninterrupted intrusive thoughts; lasting ruminations about regret or worry produced by violent anxiety, agitation, and loneliness. Acting‐out behaviors such as deliberate self‐injury and over‐dose may also be observed during the attack. As the basic psychopathology of ADA, rejection sensitivity (RS) was revealed by a structural equation model. It is said that the presence of RS in depressive disorders implies a poor prognosis. The following biological markers for RS were reviewed in the literature: first, the involvement of the μ‐opioid receptor function in RS and, secondly, hypersensitivity of the dopamine D4 receptor (DRD4) in the medial prefrontal cortex. The latter has been suggested in fear‐conditioned animal experiments. Manipulation of the μ‐opioid receptor function together with the DRD4 function may culminate in a treatment for RS, which could contribute to the development of a treatment for TRD via the improvement of ADA.